Overcoming the challenge of land access for young farmers [Uganda] - Ayebare, Prudence (Technical Centre for Agricultural and Rural Cooperation, 2018)
The Ugandan National Farmers Federation is using the Farmers Advocacy Consultation Tool to engage and empower young farmers to lobby local governments, to provide them with available land for agricultural production. Through the programme, young farmers are coming together, discussing their agricultural concerns and acting on them effectively.